2022
DOI: 10.1002/ese3.1069
|View full text |Cite
|
Sign up to set email alerts
|

Next steps in the footprint project: A feasibility study of installing solar panels on Bath Abbey

Abstract: As part of the ongoing decarbonization of society's energy sources, it is important to shift from traditional energy sources to renewable energy sources such as wind and solar. An area that is a particular challenge is reduction of the carbon footprint of historic buildings. 1 These buildings typically have poor energy efficiencies and a disproportionate energy demand and thus a larger carbon footprint compared with more modern buildings. If society is to reach net carbon zero, reducing the carbon footprint of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Also, Imam et al [18] reported that grid-connected PV installation in a typical residential building in Saudi Arabia is feasible, based on several techno-economic indices obtained from the SAM software. Furthermore, other authors affirmed the technical and economic feasibilities of rooftop solar PV designs [19][20][21][22] and floating PV designs [23,24] for specific locations around the globe.…”
Section: Introductionmentioning
confidence: 94%
“…Also, Imam et al [18] reported that grid-connected PV installation in a typical residential building in Saudi Arabia is feasible, based on several techno-economic indices obtained from the SAM software. Furthermore, other authors affirmed the technical and economic feasibilities of rooftop solar PV designs [19][20][21][22] and floating PV designs [23,24] for specific locations around the globe.…”
Section: Introductionmentioning
confidence: 94%